The Progressive Muscle Relaxation Therapi Against Decreased Anxiety Levels In Second Degree Clinical Practice Students Who Were Confirmed Covid-19.: Progressive Muscle Relaxation Therapi Against Decreased Anxiety Levels In Second Degree Clinical Practice Students Who Were Confirmed Covid-19. - Titin Supriatin; Yani Trihandayani; Yani Nurhayani (Journal of Vocational Health Science, 2024)
ABSTRACT Background: Severe Acute Respiratory Syndrome Coronavirus (Covid-19) is one of the disorders of the respiratory system. Based on data on the number of Covid-19 exposures in Indonesia that were confirmed positive as many as 6,512,913 cases, patients recovered as many as 6,319,990 cases, and died 158,768 people (Ministry of Health RI, 2022). Therapi rprogressive muscle elaxation is an exercise in muscle activity, tense muscles then lower tension by performing relaxation techniques to get a feeling of relaxation. Purpose: the purpose of this progressive muscle relaxation therapi, which is to lower tension so that it is more relaxed. This study is to measure the effectiveness of progressive muscle reflexes against decreasing anxiety levels in Second degree students who are currently practicing clinically and have confirmed Covid-19. The population used was Second degree students who were confirmed with Covid-19 at STIKes Ahmad Dahlan Cirebon, the sample or respondents in this study were second degree students who were confirmed with Covid-19 who were self-isolating after being confirmed with Covid-19 . Methods: In this study, quantitative research methods, using purposive sampling with quasi-experimental study pretest-posttest one group design research design. This study took from 22 students who practiced clinics and confirmed Covid-19 students who were exposed to Covid-19. At the value of the level of anxiety after being administered a progressive muscle relaxation therapi is 2.17 with a standard deviation of 0.381. The results of the statistical test obtained a p value of 0.000, then p < α where H 0 was rejected, meaning that there was a significant influence on the level of student anxiety before and after progressive relaxation. It is hoped that this research can be used as one of the implementations of nonpharmacology therapi to patients who have been confirmed with Covid-19 to reduce anxiety levels through the administration of his progressive muscle relaxation therapi. Keywords: Progressive muscle relaxation; Anxiety levels; Covid-19